2020
DOI: 10.1002/mus.26893
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Mini‐BESTest in adults with myotonic dystrophy type 1

Abstract: Introduction Myotonic dystrophy type 1 (DM1) is a multisystemic neuromuscular disease that causes balance problems. The objective of this study was to assess the construct validity of the Mini‐BESTest among adults with DM1. Methods Fifty‐nine individuals with late‐onset or adult phenotypes of DM1 were recruited. Participants performed the Mini‐BESTest, 10‐Meter Walk Test (10mWT), 6‐Minute Walk Test (6MWT), and Timed Up & Go (TUG) and were questioned on their tendency to lose balance and whether they fell in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Although correlations between CTG repeat length and the severity of symptoms are not highly robust, 29 it is well‐recognized that the number of CTG repeats decreases from the congenital to the late‐onset form of the disease 30 . The contribution of CTG repeat length in balance impairment found in this study reflects the previously published significant difference observed between adult and late‐onset phenotypes in Mini‐BESTest score 7 . Finally, the presence of self‐reported fatigue is contributing to lower balance score.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Although correlations between CTG repeat length and the severity of symptoms are not highly robust, 29 it is well‐recognized that the number of CTG repeats decreases from the congenital to the late‐onset form of the disease 30 . The contribution of CTG repeat length in balance impairment found in this study reflects the previously published significant difference observed between adult and late‐onset phenotypes in Mini‐BESTest score 7 . Finally, the presence of self‐reported fatigue is contributing to lower balance score.…”
Section: Discussionsupporting
confidence: 67%
“…However, this scale demonstrated a ceiling effect in our population, and other tests are now recommended by the International Outcome Measures in Myotonic Dystrophy type 1 (OMMYD) group including the Mini Balance Evaluation System Test (Mini‐BESTest) 6 . This test has shown evidence of validity in this population, especially in individuals with the adult phenotype, in which strong associations with walking capacity were found 7 . The influence on dynamic balance impairment of muscle strength and other factors that have a large impact on daily life such as fatigue, daytime sleepiness and other central nervous system manifestations 8‐14 remains unknown.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations